Alginate oligosaccharides increase boar semen quality by affecting gut microbiota and metabolites in blood and sperm - Han, Hui; Zhou, Yexun; Xiong, Bohui; Zhong, Ruqing; Jiang, Yue; Sun, Haiqing; Tan, Jiajian; Zhang, Bin; Guan, Chang; Schroyen, Martine; Chen, Liang; Zhao, Yong; et al. (Frontiers in Microbiology, 2022)
Alginate oligosaccharides (AOS), natural polymers from brown seaweeds (such as Laminaria japonica, Undaria pinnatifida, and Sargassum fusiforme), have been reported to possess many beneficial advantages for health. In the current study, after 9 weeks of dietary supplementation, AOS 10 mg/kg group (AOS 10) group increased boar sperm motility from 87.8% to 93.5%, p < 0.05. Moreover, AOS10 increased the relative abundances of Bifidobacterium, Coprococcus, Butyricicoccus (1.3–2.3-fold; p < 0.05) to increase the beneficial blood and sperm metabolites (1.2–1.6-fold; p < 0.05), and important sperm proteins such as gelsolin, Zn-alpha2 glycoprotein, Cation Channel Sperm-Associated Protein, outer dense fiber of sperm tails, etc. (1.5–2.2-fold; p < 0.05). AOS had a long-term beneficial advantage on boar semen quality by the increase in semen volume (175 vs. 160 ml/ejaculation, p < 0.05). AOS may be used as dietary additives for improving semen quality.